Late-onset Sepsis in Preterm Infants Can Be Detected Preclinically by Fecal Volatile Organic Compound Analysis: A Prospective, Multicenter Cohort Study. (21st June 2018) - Berkhout, Daniel J C; van Keulen, Britt J; Niemarkt, Hendrik J; Bessem, Jet R; de Boode, Willem P; Cossey, Veerle; Hoogenes, Neil; Hulzebos, Christiaan V; Klaver, Ellen; Andriessen, Peter; van Kaam, Anton H; Kramer, Boris W; et al.
Abstract : Preterm infants developing late-onset sepsis could be discriminated from controls by fecal volatile organic compound analysis. Focusing on individual pathogens, fecal VOCs differed significantly between cases and controls up to 3 days prior sepsis onset. Abstract: Background: The intestinal microbiota has increasingly been considered to play a role in the etiology of late-onset sepsis (LOS). We hypothesize that early alterations in fecal volatile organic compounds (VOCs), reflecting intestinal microbiota composition and function, allow for discrimination between infants developing LOS and controls in a preclinical stage. Methods: In 9 neonatal intensive care units in the Netherlands and Belgium, fecal samples of preterm infants born at a gestational age ≤30 weeks were collected daily, up to the postnatal age of 28 days. Fecal VOC were measured by high-field asymmetric waveform ion mobility spectrometry (FAIMS). VOC profiles of LOS infants, up to 3 days prior to clinical LOS onset, were compared with profiles from matched controls. Results: In total, 843 preterm born infants (gestational age ≤30 weeks) were included. From 127 LOS cases and 127 matched controls, fecal samples were analyzed by means of FAIMS. Fecal VOCs allowed for preclinical discrimination between LOS and control infants. Focusing on individual pathogens, fecal VOCs differed significantly between LOS cases and controls at all predefined time points. Highest accuracy rates were obtained for sepsis caused by Escherichia coli, followed by sepsis caused by Staphylococcus aureus and Staphylococcus epidermidis . Conclusions: Fecal VOC analysis allowed for preclinical discrimination between infants developing LOS and matched controls. Early detection of LOS may provide clinicians a window of opportunity for timely initiation of individualized therapeutic strategies aimed at prevention of sepsis, possibly improving LOS-related morbidity and mortality.